Factors Associated With Low Use Of Implant Contract In Mother's - Safitri, Mey Elisa; Us, Hafsah; Br Sembiring, Julina (Journal of Midwifery and Nursing, 2024)
Implant is called subcutaneous contraceptives; the place is under the skin on the upper arm and inserted under the skin of the inner upper arm. This study aimed to determine the factors associated with the low use of implants contraceptive in maternal at the Independent Practice of Midwife Hj. Nurasiah Tanjong Mulieng Village, Syamtalira Aron District, North Aceh Utara. The design of this study used an analytic survey using a cross-sectional approach. The population was maternal who used contraceptives were 30 respondents, and all were taken as the sample using the total population technique. The independent variables in this study were knowledge, attitudes, and husband's support. The research instrument was a questionnaire. Data analysis techniques used univariate and bivariate analyses. showed that there was a relationship between knowledge and low use of implant contraceptive with p-value = .007, there was an attitude relationship with low use of implant planning with a p-value = .032, there was a relationship between husband's support and low use of implant planning with p-value = .007. Conclusion of this study is that there is a relationship between knowledge, attitudes, and support of husbands and the low use of implant planning at the Independent Practice of Midwife Hj. Nurasiah Tanjong Mulieng Village, Syamtalira Aron District, North Aceh Utara. It is hoped that health workers will provide information about the benefits and benefits of using implant contraceptives